PELATIHAN GEJOG LESUNG DI SANGGAR SANGIR, SEBAGAI ASET WISATA DI SITUS PURBA SANGIRAN - Dwi Rahmani (Abdi Seni, 2019)
The community service program carried out in Sanggar Sangir is expected to be hold continuously, as a means to enhance the existence of traditional arts. In addition, strategically it also means for lecturers to socialize the Indonesian Institute of Arts (ISI) Surakarta. Finally, the activities can influence input more significantly, both in quality and quantity. The activities carried out were more focused on Gejog Lesung training collaborated with tabuhan Gejog Lesung, dance movements and theater for Gejog Lesung Sanggar Sanggir arts groups in Purba Site, Sangiran Sragen Regency. The material and results of the dance training represent types of tabuhan Gejog Lesung, various dance movements and dialogues in the theater. The training produces a form of repertoire aimed to be a tourism package in Purba Site, Sangiran, Sragen Regency. The training methods used in the Gejog Lesung training process include: dialogical methods, group investigations, drilling, and creative forms. The training results show the form of the activities implementation represented by Gejog Lesung art training combined with the movements or dance, vocal, and karawitan as well as dramaturgy or theatrical arts.Keywords : Training, Gejog Lesung.